Structure activity relationship studies on cytotoxicity and the effects on steroid receptors of AB-functionalized cholestanes - Rárová, Lucie; Steigerová, Jana; Kvasnica, Miroslav; Bartůněk, Petr; Křížová, Kateřina; Chodounská, Hana; Kolář, Zdeněk; Sedlák, David; Oklestkova, Jana; Strnad, Miroslav (The Journal of steroid biochemistry and molecular biology, 2016)
Structure-activity relationship analysis and profiling of a library of AB-functionalized cholestane derivatives closely related to brassinosteroids (BRs) were performed to examine their antiproliferative activities and activities on steroid hormone receptors. Some of the compounds were found to have strong cytotoxic activity in several human normal and cancer cell lines. The presence of a 3-hydroxy or 3-oxo group and 2,3-vicinal diol or 3,4-vicinal diol moiety were found to be necessary for optimum biological activity, as well as a six-membered B ring. According to the profiling of all steroid receptors in both agonist and antagonist mode, the majority of the cholestanes were weakly active or inactive compared to the natural ligands. Estrogenic activity was detected for two compounds, two compounds possessed antagonistic properties on estrogen receptors and seven compounds showed agonistic activity. Two active cholestane derivatives were shown to strongly influence cell viability, proliferation, cell cycle distribution, apoptosis and molecular pathways responsible for these processes in hormone-sensitive/insensitive (MCF7/MDA-MB-468) breast cancer cell lines.
Keywords: viabilita buněk; protinádorové látky; Cholestane derivatives; Cell Line, Tumor; steroidní receptory; Structure-Activity Relationship; Drug Screening Assays, Antitumor; cholestany; Cell Survival; Inhibitory Concentration 50; Structure-activity relationship; vztahy mezi strukturou a aktivitou; lidé; Receptors, Steroid; Humans; Antiproliferative activity; Cholestanes; Cell Cycle; Cell cycle; apoptóza; screeningové testy protinádorových léčiv; inhibiční koncentrace 50; buněčný cyklus; nádorové buněčné linie; Steroid receptor; Apoptosis; Antineoplastic Agents